Incidental Finding of Microfilaria in Submental Lymph Node Cytology: A Rare Case - Vaidehi Nagar; Vibha Patel; Sharad Gor (Tropical Journal of Pathology and Microbiology, 2024)
Filariasis is a worldwide public health concern. It is frequently examined in peripheral smears obtained from overnight sample collection. In cytology smears, microfilariae are rarely detected, despite their considerable incidence. It is rare for a lymph node to appear as a filarial nodule. Furthermore, it is unusual for lymph node fine needle aspiration cytology (FNAC) to reveal microfilariae. We would like to share the instance of a patient who had submental lymph node swelling and incidentally found microfilariae. For 10–15 days, the patient had a 2 x 2 cm enlargement of the submental lymph node along with a complaint of weight loss. Enlarged lymph nodes in the submental area were seen in the USG-neck region. Her condition was tentatively identified as lymph node swelling that was still being assessed. However, microfilariae were unintentionally discovered during the FNAC of the lymph node. When filariasis does not exhibit any clinical symptoms, FNAC can help identify microfilariae in the lymph node.